Young adult marijuana use: The influence of individual differences and legalization. (15th April 2019) - Parnes, Jamie E.; Rahm-Knigge, Ryan L.; Smith, Joey K.; Conner, Bradley T.
Abstract: In 2014, recreational marijuana use became legal for adults over 21 in Colorado. When this law was implemented, the potential health risks related to legal recreational marijuana use were unknown. Certain populations, including high-risk adolescents (i.e., adolescents schematic for personality traits predicting substance misuse, such as sensation seeking), and individuals identifying as sexual minorities, may be especially vulnerable to negative health outcomes associated with marijuana use. Based on previous research, two hypotheses were tested. First, facets of sensation seeking (i.e., risk and experience seeking) would moderate marijuana use before and after legalization and in underage and of-age participants. Second, sexual orientation would have a quadratic relation with marijuana use. Data collected from undergraduate students ( N  = 5241) at a Colorado university were used to test study hypotheses. Results indicated experience seeking negatively predicted past 30-day use while risk seeking positively predicted use for underage individuals. Morever, a significant interaction was found whereby being underage and high in risk seeking predicted increased use. As hypothesized, a quadratic relation was found between sexual orientation and past month use. Findings reported herein provide clarification of the relevance of individual risk factors on marijuana use in a state where recreational marijuana use is legal.